Temperature influences on interactions among aflatoxigenic species of Aspergillus section flavi during maize colonization - Ching'anda, C.; Atehnkeng, J.; Bandyopadhyay, R.; Callicott, K.; Orbach, Michael J.; Mehl, H.L.; Cotty, P.J. (Frontiers Media, 2021)
Fungal species within Aspergillus section Flavi contaminate food and feed with aflatoxins. These toxic fungal metabolites compromise human and animal health and disrupt trade. Genotypically and phenotypically diverse species co-infect crops, but temporal and spatial variation in frequencies of different lineages suggests that environmental factors such as temperature may influence structure of aflatoxin-producing fungal communities. Furthermore, though most species within Aspergillus section Flavi produce sclerotia, divergent sclerotial morphologies (small or S-type sclerotia vs. large or L-type sclerotia) and differences in types and quantities of aflatoxins produced suggest lineages are adapted to different life strategies. Temperature is a key parameter influencing pre- and post-harvest aflatoxin contamination of crops. We tested the hypothesis that species of aflatoxin-producing fungi that differ in sclerotial morphology will vary in competitive ability and that outcomes of competition and aflatoxin production will be modulated by temperature. Paired competition experiments between highly aflatoxigenic S-type species (A. aflatoxiformans and Lethal Aflatoxicosis Fungus) and L-type species (A. flavus L morphotype and A. parasiticus) were conducted on maize kernels at 25 and 30°C. Proportions of each isolate growing within and sporulating on kernels were measured using quantitative pyrosequencing. At 30°C, S-type fungi were more effective at host colonization compared to L-type isolates. Total aflatoxins and the proportion of B vs. G aflatoxins were greater at 30°C compared to 25°C. Sporulation by L-type isolates was reduced during competition with S-type fungi at 30°C, while relative quantities of conidia produced by S-type species either increased or did not change during competition. Results indicate that both species interactions and temperature can shape population structure of Aspergillus section Flavi, with warmer temperatures favoring growth and dispersal of highly toxigenic species with S-type sclerotia.